Management Waste Plastic Become Useful Items - Wicaksono, Athur Wahyu; Wibowo, Muhammad Yusuf; Prastiwi, Arlinda Bayu; Sulistyaningrum, Bety; Setyari, Fidya Peni; Azizah, Aurora Sylva Brilianta Nurul; Hasanah, Nely Uswatun; Hufroni, Muhammad; Rumrapuk, Juanita T D; Adani, Salma Putri; Vallent, Ellyta Fernanda Dwi; Sakti, Adinda Oktaviani; Rachmawati, Rina (Jurnal Abdimas, 2023)
Use plastic in a way continously will become serious problem in Indonesia. Plus, plastic produce a number of dangerous substances for health man. Processing waste plastic is effort For reduce rubbish plastic to the minimum possible done through cycle repeat. Amount big rubbish plastic all around environment give rise to idea For use it become product creative who has mark benefit for residents in Brangkal Village. From the observations that have been made done, known problem that is lack of understanding For manage waste plastic become product useful, therefore That A movement required For educate and provide Skills to public For manage rubbish plastic. The purpose of activity This is For give socialization and giving training to the people of Brangkal Village, especially PKK mothers for recycle repeat rubbish plastic become product craft form ecobricks and flower pots. Implementation activities, ie done Forum Group Discussion, then give socialization and skills practical For make product from rubbish plastic. Expected end result is awareness from public about danger use stack trash and improve Skills For manage rubbish plastic become product beneficial.